Evolution of Embryology from Rational Science to Evidence-based Science - Sabba Saltanat; Wasim Ahmad; Abdul Ansari; Arshad Jamal (Journal of Research on History of Medicine, 2024)
The process of embryogenesis has long fascinated scholars, both in ancient Unani medicine and modern science, as it holds the key to the formation and development of life. In Unani medicine, the understanding of embryogenesis is deeply rooted in the philosophy of life, emphasizing the importance of reproduction for species survival. This article delves into the Unani perspective on embryogenesis, highlighting the role of Manī (semen) and the interplay of Arkān (elements) in shaping the development of the embryo. Unani scholars have expounded on various aspects of embryogenesis, including the formation of essential organs, sex differentiation, and the roles of Quwwat tanasuliyya (reproductive faculty) in Manī production and fertilization. They also described a holistic view of embryonic development, from the formation of the Zubda (zygote) to the differentiation of vital organs, aligning with some principles in modern embryology.This article explores striking similarities between Unani and modern scientific concepts of embryogenesis, such as gastrulation, umbilical vessels, and sex differentiation. Additionally, it discusses aspects like quickening, lactational amenorrhea, and foetal presentation, where Unani insights align with contemporary medical knowledge.All the relevant literature on Unani medicine has been evaluated, assessed and analysed based on classical texts. Additionally, several papers in this regard were also searched using search engines, namely PubMed, Google Scholar, and ScienceDirect.The evolution of embryology as a scientific discipline has seen significant transformations, progressing from its early rudimentary stages to a more evidence-driven approach. This shift towards empirical science becomes readily apparent when examining the historical trajectory of embryological development.